Genetic Diseases That Predispose to Early Liver Cirrhosis. (14th July 2014) - Scorza, Manuela; Elce, Ausilia; Zarrilli, Federica; Liguori, Renato; Amato, Felice; Castaldo, Giuseppe
Abstract : Inherited liver diseases are a group of metabolic and genetic defects that typically cause early chronic liver involvement. Most are due to a defect of an enzyme/transport protein that alters a metabolic pathway and exerts a pathogenic role mainly in the liver. The prevalence is variable, but most are rare pathologies. We review the pathophysiology of such diseases and the diagnostic contribution of laboratory tests, focusing on the role of molecular genetics. In fact, thanks to recent advances in genetics, molecular analysis permits early and specific diagnosis for most disorders and helps to reduce the invasive approach of liver biopsy.